Development and validation of a scoring system for in‐hospital mortality following band ligation in esophageal variceal bleeding - Ichita, Chikamasa; Goto, Tadahiro; Okada, Yohei; Uojima, Haruki; Iwagami, Masao; Sasaki, Akiko; Shimizu, Sayuri (Digestive endoscopy, 2024)
Objectives We aimed to develop and validate a simple scoring system to predict in‐hospital mortality after endoscopic variceal ligation (EVL) for esophageal variceal bleeding. Methods Data from a 13‐year study involving 46 Japanese institutions were split into development (initial 7 years) and validation (last 6 years) cohorts. The study subjects were patients hospitalized for esophageal variceal bleeding and treated with EVL. Variable selection was performed using least absolute shrinkage and selection operator regression, targeting in‐hospital all‐cause mortality as the outcome. We developed the Hospital Outcome Prediction following Endoscopic Variceal Ligation (HOPE‐EVL) score from β coefficients of multivariate logistic regression and assessed its discrimination and calibration. Results The study included 980 patients: 536 in the development cohort and 444 in the validation cohort. In‐hospital mortality was 13.6% and 10.1% for the respective cohorts. The scoring system used five variables: systolic blood pressure (<80 mmHg: 2 points), Glasgow Coma Scale (≤12: 1 point), total bilirubin (≥5 mg/dL: 1 point), creatinine (≥1.5 mg/dL: 1 point), and albumin (<2.8 g/dL: 1 point). The risk groups (low: 0–1, middle: 2–3, high: ≥4) in the validation cohort corresponded to observed and predicted mortality probabilities of 2.0% and 2.5%, 19.0% and 22.9%, and 57.6% and 71.9%, respectively. In this cohort, the HOPE‐EVL score demonstrated excellent discrimination ability (area under the curve [AUC] 0.890; 95% confidence interval [CI] 0.850–0.930) compared with the Model for End‐stage Liver Disease score (AUC 0.853; 95% CI 0.794–0.912) and the Child–Pugh score (AUC 0.798; 95% CI 0.727–0.869). Conclusions The HOPE‐EVL score practically and effectively predicts in‐hospital mortality. This score could facilitate the appropriate allocation of resources and effective communication with patients and their families.